Development of hedonic-based price indexes for Kuala Lumpur office sector / Aina Edayu Ahmad - Aina Edayu, Ahmad (2015)
The recognition by the IMF on the importance of commercial property price index motivates this study, which attempts to develop the first commercial property price index in the country, in specific the Kuala Lumpur Office Price Index (KL-OPI). The transactions data used in the study are sourced from the National Property Information Centre (NAPIC), spanning from 2006 to 2011, comprising office lots in purpose-built office buildings in Kuala Lumpur. At the initial point of the study, more than 6,000 transactions data are utilised. Having gone through the cleansing and validation process, the final data set comprises 3,247 transactions. The transaction-based methodology, namely the Hedonic technique is employed based on the review carried out on literature as well as in practice. Furthermore, the familiarity of the industry with Hedonic technique as employed in Malaysian House Price Index and Purpose-Built Office Rental Index provides another platform justifying the employment of the technique for KL-OPI. Three hedonic price models are examined, which are the Conventional Hedonic Price Model, the Laspeyres Time-Varying Parameter Hedonic Price Model and the Chained Time-Varying Parameter Hedonic Price Model. The study reveals that all the three Hedonic Price Models are plausible to be employed in modelling KL-OPI. In order to determine the degree of precision of the models, Signal-to-Noise Ratio is used. The results show that though the three Hedonic Price Models have quite similar predictive power, the Conventional Hedonic Price Model records the best precision performance. This indicates that the Conventional is deemed as the most suitable model for KL-OPI.